Convergence of functional areas in information operations - Brett van Niekerk (South African Journal of Information Management, 2015)
Background: Contemporary technology and its rapid rise to a ubiquitous nature are affecting the way in which technology is used. This holds implications for military information operations and information warfare concepts as the previously separate functional areas are increasingly overlapping due to the increased convergence of information technology. Objective: The aim of the article is to illustrate the convergence of the functional areas of information operations through the use of reported examples and descriptive models.